A photocatalyst prepared by NiCo2O4/CNQD-modified carbon fabric heterojunction enhanced visible-light-driven photocatalytic degradation of methyl orange. Issue 17 (7th April 2022) - Liu, Na; Li, Xuefei; Wang, Yue; Zhu, Bolin; Tian, Ye; Lang, Jihui; Yang, Jinghai
Abstract : A novel photocatalyst cobalt nickel tetroxide (NiCo2 O4 )/g-C3 N4 quantum dot (CNQD) heterojunctions was successfully prepared on carbon cloth. Abstract : Herein, we report a novel photocatalyst cobalt nickel tetroxide (NiCo2 O4 )/g-C3 N4 quantum dot (CNQD) heterojunctions on a carbon cloth (CC). NiCo2 O4 nanosheets and NiCo2 O4 /CNQDs were grown on the carbon cloth (CC) by electrodeposition and calcination. The addition of CNQDs greatly improved the photocatalytic activity under visible light. Under the irradiation of visible light, NiCo2 O4 /CNQDs/CC and NiCo2 O4 /CC photocatalyst could remove 93% and 59% methyl orange (MO) in 60 minutes, respectively. After 5 cycles, the photocatalyst activity did not decrease distinctly. High-performance CC photocatalysts have broad application prospects in wastewater treatment, and material design strategies can be extended to other major fields, such as water purification, self-purification, antifouling and sterilization.